Golput dan Pemilu di Indonesia - Yanuarti, Sri (Jurnal Penelitian Politik, 2009)
The percentage of non voting behavior known as Golput in Indonesia was inceasing from one election period to another period In the New Order era the reasons behind Golput were political such as the election was not conducted based on democratic principles the bureaucracy and state apparatus were not neutral and systematic intimidation by government to create victory for Soeharto regime While the increasing number of non voting behavior Golput in 2004 election was caused by people s disappointment to political institution whether parliament orpoliticalparties The decayed assessment to executive institution performance president andjudicative institution judicature also became pull factors for society not to participate in the election In 2009 election however the most dominantfactor that loweredpeople s voting participation was the inefficiency of the general election committee KPU performance This has made many people who have the right to vote were not on the list This paper tries to describe Golputphenomenon in Indonesian election from one period to another including the causal factors of it.